SINTESIS PREKURSOR SENYAWA 2-AMINOBUTYRIC ACID (ABA) DENGAN STARTING MATERIAL MONOSODIUM GLUTAMATE (MSG) - Syarifah, Dewi; Slamet, Slamet; Wirasti, Wirasti; Mugiyanto, Eko (Prosiding University Research Colloquium, 2018)
The aim of the research is to synthesize the compound of Precursor of ABA from MSG the starting material by structural modification as well as to determine the characteristics and physical properties of the synthesis compound. It was done by modification of chemical structure starting with glutamic acid isolation from MSG. Then it isolate reacted with AlCl3 to obtain the ABA compound precursor. The rendemen was 18.5%, of synthesis identification obtained of white powder, odorless, dissolves in hot water and melt at a temperature of 187-189 0C. The UV-Vis spectrophotometry showed that the synthesis process formed a new compound. Confirm with HPLC analysis.